Pengaruh Parameter Number Of Excitation (NEX) Terhadap SNR - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
Abstract This research aims to observe the influence of Number of Excitation (NEX) to both parameters the Signal to Noise Ratio (SNR) and the scanning time when performing the MR neck . Some MR scan parameters (TR, TE, FOV, slice thickness, matrix, flip angle and bandwidth) are strictly under controlled. All SNR data, due to the 6 NEX variations (NEX 1 to NEX 6), are required by comparing the ROI's intensity between the noise background and the areas of corpus and spinal cord on the images. The scan times are also recorded for each of the NEX variations being observed. In conclusion, increasing NEX values will simultaneously rise the SNR and the scanning time. Keywords: NEX, SNR, Image MRI, Scan time